Effects of Exogenous Organic Acids on Cd Tolerance Mechanism of Salix variegata Franch. Under Cd Stress - Zhang, Songlin; Chen, Hongchun; He, Danni; He, Xinrui; Yan, Ya; Wu, Kejun; Wei, Hong (Frontiers in Plant Science, 2020)
Chelate-induction of organic acids has been recognized to enhance metal uptake and translocation in plants, but the underlying mechanism remains unclear. This study aimed to examine the effects of three exogenous organic acids (citric, tartaric and malic acid) on Cd tolerance mechanism in Salix variegata under Cd stress. Plant biomass, antioxidant enzymes, non-protein thiol compounds (NPT) content, and the expression of candidate genes associated with Cd accumulation and tolerance were determined. Results showed that Cd significantly inhibited plant biomass but stimulated the activity of antioxidant enzymes in the roots and leaves, whilst the lipid peroxidation increased as well. Respective addition of three organic acids greatly enhanced plant resistance to oxidative stress and reduced the lipid peroxidation induced by Cd, with the effect of malic acid showing greatest. The addition of organic acids also significantly increased the content of glutathione (GSH) in the root, further improving the antioxidant capacity and potential of phytochelatin (PC) biosynthesis. Moreover, Cd induced the expression level of candidate genes in roots of S. variegata. The addition of three organic acids not only promoted the expression of candidate genes but also drastically increased Cd accumulation in S. variegata. In summary, application of citric, tartaric or malic acid alleviated Cd-imposed toxicity through the boost of enzymatic and non-enzymatic antioxidants and candidate gene expression while their effects on Cd tolerance and accumulation of S. variegata differed.